Innovative cultural care training: the impact of flipped classroom methods on critical cultural competencies in psychiatric nursing: a quasi-experimental study - Mahdiyeh Sarvarizadeh; Sakineh Miri; Fatemeh Darban; Jamileh Farokhzadian (BMC, 2024)
Abstract Introduction Healthcare systems are encountering a growing number of diverse and multicultural clients due to globalization and migration. To effectively address the challenges associated with cross-cultural interactions, nurses require a comprehensive framework of critical cultural competencies. One potential approach to enhancing these competencies in mental health care settings is to use innovative methods such as the flipped classroom in cultural care training programs. This study evaluated the effect of using the flipped classroom method in cultural care training on the critical cultural competencies of nurses working in a psychiatric hospital. Methods This quasi-experimental study involved 70 nurses working in a psychiatric hospital affiliated with the Kerman University of Medical Sciences in southeastern Iran. Through random sampling, the nurses were allocated into two groups of intervention (n = 35) and control (n = 35). The intervention group participated in a cultural care training program using the flipped classroom method, which consisted of four sessions conducted over a four-week period. To evaluate the nurses' critical cultural competence, the Almutairi's Critical Cultural Competence Scale was administered before the training and again one month later. Results The study findings indicated no significant differences in the scores of critical cultural competencies between the intervention group (4.53 ± 0.64) and the control group (4.73 ± 0.42) during the pre-test stage (t = 1.53, p = 0.13). Both groups had a similar perception of critical cultural competencies, which was not particularly positive. However, in the posttest stage, the intervention group (5.33 ± 0.49) demonstrated a significant increase in critical cultural competencies compared to the control group (4.75 ± 0.44) (t = 5.14, p = 0.001). Conclusion The study results indicated that the use of the flipped classroom method in the cultural care training program effectively enhanced the critical cultural competencies of nurses. Given the importance of cultural care in both physical and psychiatric care settings for multicultural clients, it is crucial for nurses to receive ongoing in-service education that utilizes innovative and active methods such as the flipped classroom.